The Moves of Indonesian Application Letters - Sri Hapsari Wijayanti (Lingua Cultura, 2017)
Job application letter is one of many types of written communication. Every context has its own way to write application letter. This article aimed to know the pattern of moves of solicited and unsolicited job application letters, as well as to identify the structure patterns of moves and language used in Indonesian application letters generally. The corpus were 62 application letters. The data were analyzed by using quantitative and qualitative descriptive methods. The research finds that the Indonesian application letters consist of nine obligatory moves: opening salutation, offering candidature, introducing candidature, promoting candidature, enclosing documents, willingness to action, stressing the facts, thanking, and closing salutation. The movement structure has similarity with the application letter from other countries as previous studies. The difference lies in the label of used terms. The implicitness and inability to express self-quality could be referred to the Indonesian culture known as modesty and inhibition in telling about oneself.